The Relationship Of LBW History And Immunization Provision With The Incidence Of Stunting In Toddlers - Jeanette T. Momongan; Nurdiana, Nurdiana; Masfufah, Masfufah (Sean Institute, 2024)
Stunting is a condition that causes physical and mental health problems in children. In Indonesia, the prevalence of stunting reached 22.3%, with a target of reducing it to 14% by 2024. Factors that cause stunting include obesity, malnutrition, and poor nutrition. The purpose of this study was to identify the relationship between the history of Low Birth Weight (LBW) and immunization provisions with the incidence of stunting in toddlers aged 2-3 years in the Pantoloan Health Center working area. This study used a case control design with a backward looking approach. The population in the study were toddlers aged 24-36 months with a sample of 37 case groups and 37 control groups. Of the 74 respondents, it was found that 37 respondents in the case and control groups, 35 respondents each with a history of LBW and 2 respondents who did not have a history of LBW.Of the 37 respondents who experienced stunting, 22 of them were given complete basic immunization and 15 respondents did not get complete immunization. There is no significant relationship between LBW history and the incidence of stunting in children aged 2-3 years in the Pantoloan Health Center Working Area. However, there is a significant relationship between the history of complete basic immunization and the incidence of stunting in children aged 2-3 years in the Pantoloan Health Center Working Area.